Common frame of reference and existing EC contract law - Schulze, Reiner (Sellier. European Law Publishers, 2008)
HauptbeschreibungThe Draft Common Frame of Reference (DCFR) is just published. Now the creation of the final Common Frame of Reference (CFR) is one of the most important issues in the field of European Private Law. The volume discusses the key question as to what extent the CFR can and should reflect existing EC Contract Law, and to what extent the DCFR has already incorporated the acquis communautaire. The contributions to this volume try to provide answers to this question by analyzing different controversial areas such as the conclusion and content of the contract (pre-contractual duties, n.